A román állam területi kialakulásának története IV. Nagy-Románia születése 1918-1920 - Gulyás, László; Csüllög, Gábor (Közép-Európai Közlemények, 2016)
European states are of various ages. The formation of the statehood of some of them took place in the Middle-Ages, and they have existed in dynastic relations, though in different ways, ever since. Others are young states which have become independent statehoods in the 19th and 20th centuries, either by breaking away from earlier states or by transforming their dependent and partial statehood in opposition to power politics. Such areas in Europe are the Balkan and Eastern-Europe, among whose young states Romania stands out because of the special historical development of its statehood and its territorial changes. The Romanian state became an independent European state over several historical periods, by building from several territorial bases, and through various kinds of political dependence, at the end of the 19th century. Later on, it grew its territory several times as a result of its peculiar 20th century politics. In the fourth section of our six part series we present the detailed history of the Romanian state from the peace treaty of Bucharest (May of 1918) till the start of peace conference of Versailles (January of 1919).